Предмет: Алгебра,
автор: Magicka
Упростите выражение:
а) (a-2)(a^2+a-1)-a^2(a-1)
б) (3-p)(9+3p+p^2)-(1-p^3)
Ответы
Автор ответа:
0
a) a^3-2^3-a^3+a²=a²-8
b) 3^3-p^3-1+p^3=27-1=26
b) 3^3-p^3-1+p^3=27-1=26
Автор ответа:
0
a)(a-2)(a²+a-1)-a²(a-1)=a³+a²-a-2a²-2a+2-a³-a²=-3a+2
б)(3-p)(9+3p+p²)-(1-p³)=27+9p+3p²-9p-3p²-p³-1+p³=27-1=26
б)(3-p)(9+3p+p²)-(1-p³)=27+9p+3p²-9p-3p²-p³-1+p³=27-1=26
Похожие вопросы
Предмет: Математика,
автор: aksenovaula966
Предмет: Қазақ тiлi,
автор: tolegentolegen997
Предмет: Информатика,
автор: tanyacherepanova1808
Предмет: Литература,
автор: lowa858